Spin polarised quantum conductance in 1D channels - Henry Montagu; Ian Farrer; David Ritchie; Sanjeev Kumar (Applied Physics Express)
We report the experimental observation of a spin-polarised conductance plateau at e ^2 / h in a clean one-dimensional (1D) quantum wire defined by back-gated, split gate devices on a GaAs/AlGaAs heterostructure in the absence of a magnetic field. The 1D devices were fabricated using standard lithography techniques consisting of split gates, and a custom-designed back gate allows for the modulation of carrier density within the 1D channel. The differential conductance shows regular quantised plateaus in units of 2 e ^2 / h as a function of back gate voltage, including the observation of the 0.7(2 e ^2 / h ) conductance anomaly. The 0.7 anomaly, on reducing the charge carrier concentration, gradually converts into a 0.5(2 e ^2 / h ) structure, indicating the lifting of spin degeneracy in the absence of a magnetic field. Our results suggest the potential of low-density 1D devices for applications in spintronics and quantum electronics.